196k views
4 votes
Solve only for x: 3(x-y)=8(x+z)

User DVarga
by
5.6k points

2 Answers

2 votes

Answer:

Explanation:

3(x - y) = 8(x + z)

3x - 3y = 8x + 8z

-3y - 8z = 8x - 3x

-3y - 8z = 5x

(-3y - 8z) / 5 = x ....or could also be written like : x = -3/5y - 8/5z

User Paul Batum
by
6.0k points
1 vote

Answer:

x=-8z/5 - 3y/5

Explanation:

distributive prop

3x-3y=8x+8z

isolate x by moving 8x to the left, and -3y to the right

-5x=3y+8z

divide by -5 on both sides.

x=-8z/5 - 3y/5

User Baskren
by
5.8k points